Media Video Informasi Dan Promosi Pada SMA Islamic Centre Kota Tangerang - Syafnidawati Syafnidawati; Sella Sella (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2019)
The purpose of this research is to know the value of effectiveness in using a media promotion and information as means of supporting programs of promotion and information on Islamic HIGH SCHOOL in the Centre of the city of Tangerang. With regard to solving problems regarding HIGH SCHOOL understanding of the Islamic Centre City of Tangerang in particular regarding promotion and information that aims to introduce a school identity and overall information associated therein and about the promotion, for it presented the design of a media profile of the school-based video. In preparing the production of video media profile HIGH SCHOOL Islamic Centre City of Tangerang.